2009
DOI: 10.1186/bcr2230
|View full text |Cite
|
Sign up to set email alerts
|

Determination of HER2 phosphorylation at tyrosine 1221/1222 improves prediction of poor survival for breast cancer patients with hormone receptor-positive tumors

Abstract: Introduction High expression of total HER2 protein confers poor prognosis for breast cancer patients. HER2 is a member of the HER family consisting of four receptors, HER1 to HER4. HER receptor activity is regulated by a variety of mechanisms, and phosphorylation of the C-terminal part of the HER receptors is a marker for active signaling. The importance of phosphorylation and thereby activation of the HER1 to HER4 receptors, however, has not been investigated concomitantly in breast tumors. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 49 publications
(78 reference statements)
8
72
1
Order By: Relevance
“…However, the phosphorylated tyrosine 1248 of Her-2 was associated with BCR, suggesting that IHC evaluation of the phosphorylated form is better than the standard Her-2 test, which is not clinically used for prostate cancer patients because of a lack of reliability and association with outcome. Interestingly, similar results have been found in breast cancer tissue (Thor et al, 2000;Cicenas et al, 2006;Frogne et al, 2009) when staining of tyrosine 1221/1222 was compared with that of total Her-2. Further studies in larger cohorts would be necessary to validate this initial observation and determine the validity of phospho-Her-2 staining for clinical use in prostate cancer.…”
Section: Discussionsupporting
confidence: 80%
“…However, the phosphorylated tyrosine 1248 of Her-2 was associated with BCR, suggesting that IHC evaluation of the phosphorylated form is better than the standard Her-2 test, which is not clinically used for prostate cancer patients because of a lack of reliability and association with outcome. Interestingly, similar results have been found in breast cancer tissue (Thor et al, 2000;Cicenas et al, 2006;Frogne et al, 2009) when staining of tyrosine 1221/1222 was compared with that of total Her-2. Further studies in larger cohorts would be necessary to validate this initial observation and determine the validity of phospho-Her-2 staining for clinical use in prostate cancer.…”
Section: Discussionsupporting
confidence: 80%
“…We speculate that in these cancers low levels of highly active HER2 proteins may impact on prognosis. These findings are supported by previous observations of Frogne et al [26]; however, the low percentage of pHER2?ve/HER2-ve (15.2 %) cases observed suggests that further validation is required. Nonetheless the potential impact of activation of low levels of HER2 protein on response to a number of therapies is intriguing and might, with extreme caution, be suggested as potential mechanism to explain a number of effects including the observation that some HER2 ''negative'' cases respond to anti-HER2 directed therapies [27].…”
Section: Discussionsupporting
confidence: 91%
“…We have investigated AKT, phospho-AKT (pAKT) and Stathmin. The role of phospho-AKT staining as a prognostic marker has been explored in other cancer types, such as ovarian 195,196 , breast 197,198 and cervical cancer 199 , with conflicting results: only two of these studies, those of Guo and co-workers and Wu and collaborators, showed an independent value in relation to survival.…”
Section: Immunomarkers Predicting Survivalmentioning
confidence: 99%